Planning for co-curricular design-student voice, power dynamics and threshold learning: A thematic analysis of the student perspective - Anderson, Allison; Austin, Diana; Walton, Christina; Wood, Amanda; Houlihan, Andrea; Hard, Ella; Bailey, Kealey (International Journal for Students as Partners, 2023)
A reflexive thematic analysis is applied to focus group data to understand how students experienced working in partnership with university staff and clinical professionals to co-design aspects of the curriculum. A qualitative descriptive approach is used to examine power dynamics, hierarchies, and student voice. Four themes are identified: students felt heard, students understood the relevance of and/or translation to professional practice, students described a shift in their perceived role in the project as well as shifts in hierarchical norms, and they reported feeling a sense of confidence. Insights are offered for applying the students-as-partners (SaP) framework to health education programmes. Relevant threshold learning concepts, cultural competency, and recently announced health system priorities in New Zealand are discussed and presented as both relevant and significant considerations. This analysis intends to offer a unique contribution towards health curriculum discussions, a recognised gap within the growing body of SaP literature.